How coal and geothermal energies interact with industrial development and carbon emissions? An autoregressive distributed lags approach to the Philippines. (December 2021) - Shahzad, Umer; Schneider, Nicolas; Ben Jebli, Mehdi
Abstract: While the relationship between aggregate renewables and economic growth has been extensively studied, the literature lacks examinations assessing the responses of economic and environmental indicators to geothermal energies. This caveat turns critical when the second largest geothermal energy producer worldwide remains also overlooked. This paper seeks to fill these above-mentioned gaps and proposes the first assessment of the dynamic interactions between coal energy consumption, geothermal energy consumption, industry value added and carbon emissions in the Philippines. Having provided a state-of-the-art review of the subject, our econometric procedure applies the F-Bounds test, the Autoregressive Distributed Lags and the Pairwise Granger causality test. Results support the existence of a bidirectional link among geothermal energy and aggregate income, congruent with the feedback hypothesis. Also, industry value added is found to drive coal consumption, and vice versa . Finally, geothermal energy and coal reveal a counter-intuitive positive and negative impact on carbon pollution on the short- and long-run, respectively. These results relate to the structure of the electricity supply largely dominated by fossil fuels in the Philippines and emphasize the need to further deploy geothermal energies. To meet the booming power demand from manufacturers, it is thus crucial to set up the conditions for scale effects and efficiency gains in the geothermal industry. Highlights: The nexus among coal and geothermal energies, industrial growth and CO2 is tested. A bidirectional link among coal and geothermal energy is found with income. A counter-intuitive positive impact of geothermal energy on CO2 is revealed. Geothermal energies should be expanded to reconcile economic and carbon targets.